In-situ-Investigation of Enzyme Immobilization on Polymer Brushes - Koenig, Meike; König, Ulla; Eichhorn, Klaus-Jochen; Müller, Martin; Stamm, Manfred; Uhlmann, Petra (Frontiers in Chemistry, 2019)
Herein, we report on the use of a combinatorial setup of quartz-crystal microbalance with dissipation monitoring and spectroscopic ellipsometry to comprehensively investigate the covalent immobilization of an enzyme to a polymer layer. All steps of the covalent reaction of the model enzyme glucose oxidase with the poly(acrylic acid) brush by carbodiimide chemistry were monitored in-situ. Data were analysed using optical and viscoelastic modeling. A nearly complete collapse of the polymer chains was found upon activation of the carboxylic acid groups with N-(3-Dimethylaminopropyl)-N'-ethylcarbodiimide and N-Hydroxysuccinimide. The reaction with the amine groups of the enzyme occurs simultaneously with re-hydration of the polymer layer. Significantly more enzyme was immobilized on the surface compared to physical adsorption at similar conditions at the same pH. The pH responsive swelling behavior was found to be almost not affected by the presence of the enzyme.